HIV and women in the USA: what we know and where to go from here. Issue 10279 (20th March 2021) - Adimora, Adaora A; Ramirez, Catalina; Poteat, Tonia; Archin, Nancie M; Averitt, Dawn; Auerbach, Judith D; Agwu, Allison L; Currier, Judith; Gandhi, Monica
Summary: New diagnoses of HIV infection have decreased among women in the USA overall, but marked racial and geographical disparities persist. The federal government has announced an initiative that aims to decrease the number of new infections in the nation by 90% within the next 10 years. With this in mind, we highlight important recent developments concerning HIV epidemiology, comorbidities, treatment, and prevention among women in the USA. We conclude that, to end the US HIV epidemic, substantially greater inclusion of US women in clinical research will be required, as will better prevention and treatment efforts, with universal access to health care and other supportive services that enable women to exercise agency in their own HIV prevention and care. Ending the epidemic will also require eliminating the race, class, and gender inequities, as well as the discrimination and structural violence, that have promoted and maintained the distribution of HIV in the USA, and that will, if unchecked, continue to fuel the epidemic in the future.